GameMaker programming by example : master the development of 2D games by learning to use the powerful GameMaker language and tools provided by the GameMaker: Studio workspace and engine! /: master the development of 2D games by learning to use the powerful GameMaker language and tools provided by the GameMaker: Studio workspace and engine!. (2015) - Christian, Brian
No abstract available